Calculation of the representative temperature change for the thermomechanical design of energy piles. (March 2022) - Song, Huaibo; Pei, Huafu; Zhou, Chao; Zou, Dujian; Cui, Chunyi
Abstract: In the geotechnical design of energy piles using various methods such as simplified one-dimension analyses and finite element simulations, the pile temperature change is a crucial input parameter. The current analysis methods usually ignore the non-uniformity of temperature over the pile cross-section and adopt the maximum temperature change as the input parameter. However, this method cannot correctly describe the thermomechanical performance of energy piles and may lead to over-design. This paper provides an analytical model to determine the representative temperature change for the geotechnical design of energy piles. To this end, the expression of the average temperature change corresponding to the average strain of the pile cross-section is firstly derived according to the assumption of strain compatibility. The representative temperature change calculation approach is further proposed by introducing the thermal resistance and heat source model. Comprehensive validation of the proposed model is presented by using experimentally verified numerical simulations. Besides, climatic conditions, heat exchange pipe configurations, and pile diameter on the representative temperature change are studied. The results show that the proposed model is capable of calculating the representative temperature change effectively. Overall, the proposed model provides a reliable approach to determining the representative temperature change used in the geotechnical design of energy piles, and its feature that avoids cumbersome numerical simulations and computing make it have extensive application prospects in the geotechnical design of energy piles. Highlights: The concept and derivation process of the representative temperature change are presented. The analytical model for calculating the representative temperature change is proposed. The effect of crucial factors, such as pipe configurations and pile diameter, has been studied. Recommendations are made on the thermomechanical design for energy piles.